Implementing conservation in the Cederberg: the role of the buchu (Agathosma betulina) sector - Baard, Cynthia (Department of Environmental and Geographical Science, 2024)
Through the early 2000s, the expanded popularity of the fynbos buchu shrubs (Agathosma betulina and Agathosma crenulata) for its use in medicinal products and as an essential oil drove demand to a point where wild stocks of the species became threatened by poor management practices and over-harvesting. In response, cultivation was encouraged to augment species supplies. The impact the continued expansion of commercialisation has had on the species and its wider landscape, however, remains unknown. As a member of the fynbos family of plants, buchu is an aromatic shrub endemic to the biodiversity-rich Cape Floristic Region (CFR) found predominantly in the Western Cape, South Africa. The study aimed to contribute to a better understanding of the role actors within the buchu sector economy play in either mitigating or exacerbating threats to buchu and surrounding vegetation. Further, the study looked to determine if the activities associated with wild buchu harvesting and the expansion of monoculture buchu plantations threaten biodiversity and the interconnectedness of species within the greater fynbos habitat. To meet this aim, the study utilised a qualitative methods approach and involved semi-structured interviews with buchu producers, users, and processors across the Cederberg Municipality and with regulators operating across the Western Cape Province. The research found that the regulations and laws applying to the South African context are well positioned to effectively protect indigenous plants such as buchu, while monitoring and implementation remains challenging due to landscape and resource constraints. All buchu value chain participants provided a general understanding and accurate interpretation of the concepts of biodiversity conservation. Furthermore, participants acknowledged that the protection of biodiversity was essential to sustaining the operations and functioning of the industry itself. All domestic participants expressed a personal connection to buchu as a species and a protectionist attitude towards its existence across both the wild and cultivated environments. Value chain participants involved in farming, wild harvesting, and processing saw themselves as contributors to conservation efforts aimed at protecting the species and mitigating threats, while those further afield believed conservation should be prioritised and implemented by national or provincial management authorities. The study concludes that due to many steps of the value chain occurring within the immediate environment where the plant grows, those involved in commercialisation of the species are well positioned to become active participants in a cross-disciplinary approach to conservation implementation and biodiversity management efforts at local and regional levels and could be recommended to advise on management priorities affecting buchu and the associated landscapes as key informants, as well as to assist authorities with the implementation of associated activities.